The Effect of Person-Job Fit and Job Embeddedness on a Teacher’s Task Performance - Mulyani, Annisa Mairi; Pareke, Fahrudin Js (research, training and philanthropy institution Natural Aceh, 2024)
The quality of an institution can be seen through the task performance of its employees. Task performance can be enhanced with various supportive aspects, including fulfilling work wants and needs, individual-job fit congruence, individual and job or institutional attachment, and formal and informal relationships with coworkers. This study aims to determine how the influence of person-job fit on a teacher's job embeddedness, the influence of person-job fit on a teacher's task performance, and the influence of job embeddedness on the task performance of public junior high school teachers in Bengkulu City. The method used in this research is descriptive quantitative. The data were then analyzed descriptively to answer the research questions. One hundred fourteen respondents from various public junior high schools in Bengkulu City were taken randomly. The data collection tool used is a questionnaire instrument. Results revealed a noteworthy positive correlation between person-job fit and job embeddedness (t=10.876, p<0.05), as well as a significant positive effect on the task performance of teachers (t=5.223, p<0.05). Conversely, job embeddedness did not significantly affect teacher task performance (t=0.027, p>0.05). This study underscores the importance of prioritizing institutional leaders prioritizing employee needs fulfilment, as it serves as a vital support mechanism for enhancing task performance.